Expression of anaphylatoxin receptors on platelets in patients with coronary heart disease. Issue 2 (February 2015) - Patzelt, J.; Mueller, K.A.L.; Breuning, S.; Karathanos, A.; Schleicher, R.; Seizer, P.; Gawaz, M.; Langer, H.F.; Geisler, T.
Abstract: Objective : Inhibition of components of the complement system or of its receptors has been postulated as a concept for primary and secondary prevention in atherosclerosis and was applied in clinical trials. Although the anaphylatoxin-receptors C3aR and C5aR are commonly associated with inflammatory cells, in vitro studies suggested their expression also on platelets. Methods and Results : Expression levels of C3aR and C5aR were measured by flow cytometry in a collective of 302 patients with documented coronary artery disease (CAD) including patients with stable CAD (n = 152), unstable angina (n = 54), acute myocardial infarction (AMI; Non-ST elevation myocardial infarction, n = 70, ST elevation MI, n = 26) or healthy controls (n = 21). Patients with stable CAD, unstable angina or AMI had significantly higher expression of C5aR on platelets in comparison to healthy controls (MFI 14.68 (5.2), 14.56 (5.18) and 13.34 (4.52) versus 10.68 (3.1)); p < 0.001). In contrast, the expression of C3aR on platelets was significantly enhanced in patients with stable and unstable CAD but not in patients with AMI compared to controls. While there was a strong correlation between the soluble ligands of these receptors C3a and C5a, we observed only a weak correlation with their receptors on platelets. Similarly, agonist induced aggregation (MEA, ADP, and TRAP) showed only a weak correlation with the expression level of anaphylatoxin – receptors on platelets. Of note, the expression of both anaphylatoxin-receptors on platelets strongly correlated with platelet activation as assessed with the surface activation marker P-selectin (r = 0.47, p > 0.001 for C3aR, r = 0.76 for C5aR, p < 0.001). Likewise, we observed a positive correlation of C3aR with other molecules associated with platelet activation such as SDF-1. Conclusion : In summary, we observed a positive correlation between the expression of anaphylatoxin-receptors C3aR and C5aR with platelet activation in patients with CAD. Further investigations are needed to study the clinical and mechanistic relevance of these findings. Highlights: An inter-relationship between platelet activation and components of the complement cascade has been proposed. Previous in vitro data suggest expression of anaphylatoxin receptors C3aR and C5aR on platelets. We provide the first data on expression levels of anaphylatoxin receptors C3aR and C5aR on platelets in patients with CAD. The correlation of C3aR and C5aR with their soluble ligands was assessed in patients with CAD. A positive correlation of C3aR and C5aR with platelet activation in patients with cardiovascular disease was observed.